Potential role of biosynthesized zinc oxide nanoparticles in counteracting lead toxicity in Solanum lycopersicum L. - Zeba Azim; N.B. Singh; Shubhra Khare; Ajey Singh; Nimisha Amist; Niharika; Ravi Kumar Yadav; Imtiyaz Hussain (Plant Nano Biology, 2022)
abstract: Zinc oxide nanoparticles are synthesized through an eco-friendly route by using Vernonia cinerea (L.) leaf extract. The extract obtained from leaf functions acts as a reducing, stabilizing, and capping agent. The bio-synthesized ZnO NPs were characterized by viz. Ultraviolet-visible spectrum, Fourier transforms infrared spectrum, X-ray diffraction analysis, and Field emission scanning electron microscope. The present study explored the plausible role of bio-synthesized ZnO NPs in the mitigation of lead induced oxidative stress by investigating the growth parameters, photosynthetic pigments, protein content, nitrate reductase activity, antioxidant enzymes, etc in the tomato (Solanum lycopersicum L.) seedlings. The seedlings of Solanum lycopersicum were treated with single dose (50 mg L−1) of bio-synthesized ZnO NPs and/or in combination with lead. The bio-synthesized ZnO NPs remarkably increased germination rate, seedling vigor index, relative water content, chlorophyll content, protein, sugars, nitrate reductase activity alone, and in the combination with lead in tomato seedlings. Furthermore, the bio-synthesized ZnO NPs mitigated the deleterious impact of Pb-induced stress by up-regulation of photosynthetic machinery and stimulating the antioxidant stress markers such as superoxide dismutase, catalase, and ascorbate peroxidase in lead-induced stress. The present study concluded that the bio-synthesized ZnO NPs boost the growth performance and ameliorate the lead stress in tomato seedlings.